MYKONOS CONTENT MARKETING COMMUNICATION STRATEGY ON INSTAGRAM TOWARDS INCREASING BRAND AWARENESS - Nadia Amelia Poluan; Marlina Deliana (Journal Business Administration: Entrepreneurship and Creative Industry, 2026)
This study aims to analyze the content marketing communication strategy implemented by the Mykonos brand on Instagram in increasing brand awareness. The high use of social media in Indonesia has made Instagram a strategic platform for digital marketing communication, particularly in the increasingly competitive perfume industry. This research employs a literature review method with a descriptive qualitative approach by analyzing various scientific sources related to content marketing, digital marketing communication, and brand awareness. The Stimulus–Organism–Response (S-O-R) framework is used to explain the relationship between content as a stimulus, audience cognitive processes as the organism, and increased brand awareness as the response. The findings indicate that the effectiveness of content marketing communication strategies is influenced by content quality, visual consistency, interactivity, and storytelling. Informative, engaging, and relevant content is proven to increase audience engagement and strengthen brand recall. In addition, visual and aesthetic aspects play an important role in building a recognizable brand identity. Therefore, a well-planned, consistent, and audience-oriented content marketing communication strategy plays a significant role in increasing brand awareness in the digital era